2021
DOI: 10.3390/agronomy11071303
|View full text |Cite
|
Sign up to set email alerts
|

Considering Human Variability in the Design of Safe Interaction with Agricultural Machinery: The Case of Foldable Roll-Over Protective Structure (FROPS) Manual Handling

Abstract: The foldable roll-over protective structure (FROPS) protects the operators against fatal injuries in tractor roll-over accidents. However, a rear-mounted FROPS is often folded down or removed. In the present study, the accessible zones and grasping areas in a rear-mounted FROPS were redesigned and adapted to the 5th, 50th, and 95th European human anthropometric percentiles to enhance its correct and comfortable use. Then, a rod was proposed as a design solution to make the roll-bar grasping areas fall within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…The first feedback from the operators was positive since they declared that the PAS makes the FROPS handling easier for both operations (raising and lowering) and they confirmed that if this system will be available on the market in the future, they will be eager to apply it to their tractors. Therefore, although the number of interviewed farmers is not large, these preliminary tests can be considered valid as they are in line with similar tests among farmers on the FROPS' use, such as the research by Cremasco et al [39]. Conversely, in the initial stage of the lowering phase, the value of the force needed to lower the FROPS is slightly higher than the maximum value foreseen by the OECD Code no.…”
Section: Validationsupporting
confidence: 71%
“…The first feedback from the operators was positive since they declared that the PAS makes the FROPS handling easier for both operations (raising and lowering) and they confirmed that if this system will be available on the market in the future, they will be eager to apply it to their tractors. Therefore, although the number of interviewed farmers is not large, these preliminary tests can be considered valid as they are in line with similar tests among farmers on the FROPS' use, such as the research by Cremasco et al [39]. Conversely, in the initial stage of the lowering phase, the value of the force needed to lower the FROPS is slightly higher than the maximum value foreseen by the OECD Code no.…”
Section: Validationsupporting
confidence: 71%
“…Smallholding farmers often work in solitary conditions and, therefore, face additional issues when accidents happen and rescue is needed; on the other hand, mechanization is vital for larger farms and the dangers derived from poor interaction between workers on foot and vehicles eventually arise. Difficulty in handling protection devices can also be a major concern [2] as it adds to an existing negative attitude towards safety [3]. Furthermore, the coming of digital agriculture has highlighted how such hazards need to be mitigated or eliminated, given the increasing usage of remotely controlled vehicles and automated equipment; previous research has, in fact, already shown that safety plays a key role even at the design stage [4] and its management needs to be embedded with quality in every agricultural practice [5].…”
Section: Introductionmentioning
confidence: 99%